Unlocking Investments for Climate Resilient Agri-food Systems in Low- and Middle-Income Countries: Policy Keys to Climate Resilience - Sartas, Murat; Mayanja, Brian; Rose, Sabrina; Loboguerrero, Ana Maria; Pradhan, Melissa (International Center for Tropical Agriculture, 2024)
The severe effects of climate change are becoming increasingly common worldwide. As these effects grow more prominent, the need for investments to protect lives, economies and the environment escalates. Low- and middle-income countries face relatively more restricted access to and use of climate finance, with their populations growing at a higher rate, resulting in a disproportionate investment gap. Designing and implementing sustainable and agile climate policies and programs that shield people and nations against climate change necessitates mobilizing significant investment and employing a diverse set of financial instruments. The CGIAR Initiatives on Climate Resilience and on National Policies and Strategies for Food, Land and Water Systems Transformation, as well as national partners in Guatemala, Kenya, Morocco, the Philippines, Senegal, and Zambia have collaboratively developed, tested, and implemented multiple climate investment solutions to address the investment gap, unlocking several large-scale investments.